(untitled) (Universal International Scientific Journal, 2026)
the article examines the specific features of teaching Russian as a foreign language (RFL) in a multilingual classroom. It analyzes methodological approaches, the challenges of interference from students’ native languages, the role of intercultural communication, as well as modern didactic solutions aimed at improving the effectiveness of instruction. Practical examples of tasks and teaching techniques used in multicultural groups are also presented.